Perspectives from the Deaf Community: Representations of Deaf Identity in the Toronto Star Newspaper (2005-2010) - Bath, Paula M. C. (Université d'Ottawa / University of Ottawa, 2012)
This thesis is an analysis of the representations of Deaf identity in a major English Canadian newspaper, the Toronto Star. A qualitative case-based discourse analysis was used to examine a documented interaction between the Toronto Star and eleven Deaf community leaders and allies. This research found that the most frequent use of ‘deaf’ is metaphorical and of the non-metaphorical uses, ‘Deaf’ identity is predominantly constructed from a pathological paradigm. The findings of this research provide a valuable perspective from a non-dominate cultural group, the Canadian Deaf community, on the representation of Deaf identity in mainstream print news media. It also makes linkages between the representations of Deaf identity and the experiences of these representations by Deaf people, and links the perspectives of this cultural group to the broader body of research related to minority identity negotiation in mainstream media.
Keywords: Deaf; Identity; Representation; Media